English Learning and Resilience in a Coastal Community: A Culturally Grounded Approach in Bajo Lawele, Buton Regency - Nur Dahniar (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
This study examines an English language learning intervention for coastal children in Bajo Lawele, Buton Regency, Indonesia, by integrating resilience principles, culturally grounded learning, and community participation. The study employed a pre-experimental one-group pretest–posttest design involving 32 Bajo children aged 9–12 years. The intervention was conducted in six sessions over three weeks using storytelling with maritime themes, vocabulary games related to coastal life, and role-play based on children’s everyday experiences. Data were collected through an English proficiency test covering vocabulary, listening, and speaking micro-tasks, a resilience scale adapted from Grotberg’s framework (I Have, I Am, and I Can), classroom observations, and informal parent interviews. The findings showed positive changes in both English proficiency and learning resilience after the intervention. Vocabulary scores increased from 45.6 to 72.3, listening comprehension from 48.1 to 70.4, and speaking from 41.3 to 68.9, with the highest gain in speaking (66.8%). Improvements were also found in all resilience dimensions, especially I Can, which increased from 52.9 to 82.4 (55.7%). These findings suggest that culturally grounded and resilience-informed English learning may support language development and learner engagement among coastal children while preserving local cultural values.